Teamwork, Spirit of the Game and Communication: A Review of Implications from Sociological Constructs for Research and Practice in Ultimate Frisbee Games - Amoroso, José (2021)
Ultimate Frisbee (UF) is a non-contact, challenging, and self-promoted team sport. Its characteristics, such as the game environment and rules, appear to influence the on-the-pitch behaviour of players. This article examines the content of qualitative studies to determine if and how the unique characteristics of UF may be related to nine sociological themes, that may be identified during gameplay. These themes include the following: (a) competition and performance; (b) enjoyment; (c) communication; (d) cooperation/friendship; (e) behaviors/welfare; (f) teamwork/social skills; (g) environment/lifestyle; (h) rules/self-refereeing and (i) spirit of the Game (SOTG). The review was conducted according to PRISMA guidelines. A comprehensive search protocol was used to identify, screen, and select published research articles under a Qualitative Systematic Review (QSR). The search was occurred from 1 June to 30 December 2020 with no limitations regarding the year of publication. Original English-language papers that contained relevant data regarding sociological themes and UF were selected. As a result, nine papers were qualified to be included in the final version of QSR. The files analyzed were structured with MAXQDA. A total of 521 references were identified and selected for analysis. After the Screening (n = 301) and Eligibility (n = 71) phases, a total of 30 potential papers were selected and classified. Nine studies were included in the final analysis. The three most cited sociological themes in these studies were: communication, teamwork/social skills, and spirit of the game. Research suggests that UF involves patterns of interaction related to communication and the spirit of the game that encourage active lifestyles. Finally, we point out that UF is an appropriate sport to include in physical education classes in which the creation of positive relationships between students is the desired outcome. This topic should be explored further through interventional studies done in different contexts although the evidence suggests that UF offers players unique opportunities to experience a combination of physical activity and enjoyment.